2013
DOI: 10.1021/bi401192z
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Characterization of the Bilin Lyase CpcS from Thermosynechococcus elongatus

Abstract: Cyanobacterial phycobiliproteins have evolved to capture light energy over most of the visible spectrum due to their bilin chromophores, which are linear tetrapyrroles that have been covalently attached by enzymes called bilin lyases. We report here the crystal structure of a bilin lyase of the CpcS family from Thermosynechococcus elongatus (TeCpcS-III). TeCpcS-III is a 10-stranded beta barrel with two alpha helices and belongs to the lipocalin structural family. TeCpcS-III catalyzes both cognate as well as no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 91 publications
0
37
0
Order By: Relevance
“…Binding studies with these GtCPES variants and different phycobilins revealed a participation of Glu-136 and Arg-146 in phycobilin binding. The importance of Arg-146 or homologous amino acid residues for phycobilin binding has previously been confirmed for TeCpcS and NCpcS-III (where N is Nostoc) (23,68). Interestingly, the TeCpcS-R151G variant still bound enough PCB to confer transfer to the apoprotein CpcB in E. coli (68).…”
Section: Peb Biosynthesis In G Theta Adopted From Cyanobacteria-mentioning
confidence: 82%
See 3 more Smart Citations
“…Binding studies with these GtCPES variants and different phycobilins revealed a participation of Glu-136 and Arg-146 in phycobilin binding. The importance of Arg-146 or homologous amino acid residues for phycobilin binding has previously been confirmed for TeCpcS and NCpcS-III (where N is Nostoc) (23,68). Interestingly, the TeCpcS-R151G variant still bound enough PCB to confer transfer to the apoprotein CpcB in E. coli (68).…”
Section: Peb Biosynthesis In G Theta Adopted From Cyanobacteria-mentioning
confidence: 82%
“…The importance of Arg-146 or homologous amino acid residues for phycobilin binding has previously been confirmed for TeCpcS and NCpcS-III (where N is Nostoc) (23,68). Interestingly, the TeCpcS-R151G variant still bound enough PCB to confer transfer to the apoprotein CpcB in E. coli (68). For Glu-136, the carboxylic function might be involved in positioning of the substrate by interaction with the tetrapyrrole nitrogens, as found for bilin-binding in FDBRs (51,73,74).…”
Section: Peb Biosynthesis In G Theta Adopted From Cyanobacteria-mentioning
confidence: 84%
See 2 more Smart Citations
“…CpcS transiently binds bilins such as PCB (14). The crystal structures of a cyanobacterial CpcS (PDB code 3BDR) 5 (11,28) and a cryptophytes CPES (29) have been determined in the absence of a chromophore. They both adopt a ␤-barrel structure similar to those of fatty acid-binding proteins (FABP), a subfamily of the calycin superfamily (Pfam0116) that binds a variety of small, mostly lipophilic molecules with high selectivity (30 -32).…”
mentioning
confidence: 99%